2022
DOI: 10.1097/yic.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Repeated subcutaneous racemic ketamine in treatment-resistant depression: case series

Abstract: Interest in the use of parenteral ketamine has been increasing over the last 2 decades for the management of treatment-resistant depression (TRD). While intravenous (IV) ketamine has been the most common parenteral route of administration, subcutaneous (SC) and intramuscular options have been described. We developed a clinical treatment protocol for the use of repeated SC racemic ketamine (maximum six treatments, twice per week) in an inpatient psychiatric care setting with inclusion/exclusion criteria, dosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Interest in glutamatergic modulators began more than 15 years ago with ketamine [ 34 ], suggesting for the first time a new antidepressant mechanism that showed efficacy within hours rather than weeks. In the years that followed, many studies confirmed the initial findings and we now have ketamine in clinical practice plus the more convenient nasal esketamine [ 35 - 38 ]. Research then expanded to include similar psychoactive drugs such as the serotonergic psychedelics, especially psilocybin.…”
Section: Psilocybinmentioning
confidence: 93%
“…Interest in glutamatergic modulators began more than 15 years ago with ketamine [ 34 ], suggesting for the first time a new antidepressant mechanism that showed efficacy within hours rather than weeks. In the years that followed, many studies confirmed the initial findings and we now have ketamine in clinical practice plus the more convenient nasal esketamine [ 35 - 38 ]. Research then expanded to include similar psychoactive drugs such as the serotonergic psychedelics, especially psilocybin.…”
Section: Psilocybinmentioning
confidence: 93%
“…Ketamine is reaching a wide clinical use due to the rapid antidepressant effects [ 87 - 89 ], the preliminary evidence available suggest that it has a relevant anti-anhedonic effect with a rapid onset of action [ 50 , 90 ], thus suggesting its use in specific clinical contexts where rapid effect is needed. Within a similar drug class, much interest is now focusing on psilocybin, which has the further benefit of one point administration [ 91 ].…”
Section: Treatment Of Anhedoniamentioning
confidence: 99%
“…There is now strong support for its rapid benefit in resistant depression (Bahji et al ., 2021; Alnefeesi et al ., 2022), with evidence of being second in efficacy only to electroconvulsive therapy (Rhee et al ., 2022). Ketamine is a valuable option also in emergency situations (Pompili et al ., 2022), and recently convenient subcutaneous administration methods have been suggested (Rocha et al ., 2021; Tham et al ., 2022). However, ketamine benefits may extend to other less common clinical conditions that are quite challenging to manage.…”
mentioning
confidence: 99%